Practical results of the study of photopolymer exposure of printed circuit board topology - Nevlyudov, I.; Razumov-Frizyuk, E.; Nikitin, D.; Badaniuk, I.; Strelets, R. (ISMA, 2023)
Practical results of studies of deviations of geometric dimensions of the topological structure of printed circuit boards during photopolymer 3D exposure are presented. A series of experiments of topology exposure under different process parameters was carried out. The results of 112 samples were checked using statistical analysis and a regression model of the influence of parameters on the deviation of the geometric dimensions of conductors was built.
Keywords: photopolymer exposure; printed circuit board topology